A Novel Pathogenic Splicing Mutation of OFD1 is Responsible for a Boy with Joubert Syndrome Exhibiting Orofaciodigital Spectrum Anomalies, Polydactyly and Retinitis Pigmentosa - Chen L; Zhao MF; Deng HW; Liao M; Fan LL; Zhong QB; Wang J; Li K; Wu ZH; Yin JY (Pharmacogenomics and Personalized Medicine)
Liang Chen,1,* Mei-Fang Zhao,2,* Hui-Wen Deng,1 Min Liao,1 Liang-Liang Fan,2 Qi-Bao Zhong,3 Jun Wang,1 Ke Li,1 Zheng-Hui Wu,4,* Jian-Yin Yin1 1Department of Anesthesiology, Hunan Provincial Maternal and Child Health Care Hospital, Changsha, 410008, People’s Republic of China; 2Department of Cell Biology, School of Life Sciences, Central South University, Changsha, 410013, People’s Republic of China; 3Department of Facial Features, Hunan Provincial Maternal and Child Health Care Hospital, Changsha, 410008, People’s Republic of China; 4Department of Child Rehabilitation, Hunan Provincial Maternal and Child Health Care Hospital, Changsha, 410008, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian-Yin Yin, Department of Anesthesiology, Hunan Provincial Maternal and Child Health Care Hospital. No. 53, Xiangchun Road, Kaifu District, Changsha, 410008, People’s Republic of China, Email 357773796@qq.comAbstract: Joubert syndrome (JS) is an infrequent congenital neurodevelopmental ciliopathy, typically identified in children around the average age of 33 months. This disorder is characterized by developmental delay, cognitive impairment, and infantile hypotonia that may evolve into ataxia. Mutations in OFD1 results in Joubert syndrome with a variety of phenotypes. Here, we identified a child who presented with Joubert syndrome exhibiting orofaciodigital spectrum anomalies, polydactyly, and retinitis pigmentosa. Whole exome sequencing and Sanger sequencing revealed a splicing mutation (NM_003611.2, c.2387+1G>A) in the OFD1 gene of the patient and his mother. mRNA sequencing further confirmed this mutation. However, since the patient is homozygous and the mother is heterozygous, only the patient has the phenotype and the mother is normal. This mutation can lead to the loss of sixth coiled-coil domains of OFD1 protein, which further disrupt the ciliary signaling pathway and Hedgehog signaling pathway. This study presents a new case of JS and expands the mutant spectrum of OFD1, but also enhances our understanding of the mechanism by which OFD1 is associated with ciliosis.Keywords: Joubert syndrome, OFD1, splicing mutation, ciliosis